THE PLACE OF PEDAGOGICS IN THE SYSTEM OF PEDAGOGICAL EDUCATION OF UKRAINE IN THE HISTORICAL DISCOURSE OF IN THE 19th - EARLY 20th CENTURY - Bashkir, Olha (Educological discourse, 2017)
The peculiarities of formation and development of pedagogics as a science in the system of professional training of future teachers during the 19th - early 20th century have been found out in the article on the basis of the analysis of historical and pedagogical literature. The public need for training of pedagogical personnel has been determined to emerge during this period. That led to the development of appropriate forms of organization and the necessary scientific provision of its effectiveness (the creation of pedagogical institutes at universities, departments of pedagogy, generalization of empirical experience, development of pedagogical theory). The domestic scientists (K. Ushynskyi, S. Myropolskyi, A. Valytskyi, S. Hohotskyi, M. Lavrovskyi, T. Lubenets, F. Zelenohorskyi, B. Hrinchenko, L. Tolstoi and others) have been established to continue developing the theoretical foundations of pedagogics and implementing them in the practice of training future teachers contrary to the state policy. Attention of the scholars of the 19th - 20th century was attracted to the problem of pedagogical training of youth mentors, didactics and teaching methods, learning content in pedagogical establishments, requirements for teachers. According to scientists, the importance of theoretical training of future teachers consisted in preventing from their mistakes, waste of time; preparing for practice, facilitating the accumulation of personal experience, enriching the necessary fund of scientific information, disciplining thought and giving the ability to process pedagogical matters comprehensively, forming the teacher's ability to treat the education of the personality independently and critically. These thoughts led to the fact that pedagogics began to be taught in universities, teacher institutes and seminaries, in pedagogical courses in the early 20th century. In the 1920s educationalists (S. Ananin, M. Dadenkov, A. Hotalov-Hotlib, H. Zhurakivskyi, H. Kostiuk, N. Krupska, O. Popov, I. Sokolianskyi, S. Chavdarov and others) paid special attention to professional training of future teachers, to the necessity of understanding the very essence of pedagogical science by teacher, its current state, the main stages of development and relations with other sciences, with social relations, the surrounding life.